Plasma IGFBP-3 and IGFBP-5 levels are decreased during acute manic episodes in bipolar disorder patients - Fernández-Pereira, Carlos; Penedo, Maria Aránzazu; Alonso-Núñez, Adrián; Rivera-Baltanás, Tania; Viéitez, Irene; Prieto-González, José María; Vilariño-Vilariño, María Isabel; Olivares, José Manuel; Ortolano, Saida; Agís-Balboa, Roberto Carlos (Frontiers in Pharmacology, 2024)
Introduction: Bipolar disorder (BD) is a recurrent and disabling psychiatric disorder related to low-grade peripheral inflammation and altered levels of the members of the insulin-like growth factor (IGF) family. The aim of this study was to evaluate the plasma levels of IGF-2, insulin-like growth factor-binding protein 1 (IGFBP-1), IGFBP-3, IGFBP-5, IGFBP-7, and inflammatory markers such as tumor necrosis factor α (TNF-α), monocyte chemoattractant protein 1 (MCP-1), and macrophage inflammatory protein 1β (MIP-1β). Methods: We used the Young Mania Rating Scale (YMRS) to determine the severity of the symptomatology, while proteins were measured by enzyme-linked immunosorbent assay (ELISA). We included 20 patients with BD who suffered a manic episode and 20 controls. Some BD patients (n = 10) were evaluated after a period (17 ± 8 days) of pharmacological treatment. Results: No statistical difference was found in IGF-2, IGFBP-1, IGFBP-7, TNF-α, and MIP-1β levels. However, IGFBP-3 and IGFBP-5 levels were found to be statistically decreased in BD patients. Conversely, the MCP-1 level was significantly increased in BD patients, but their levels were normalized after treatment. Intriguingly, only IGFBP-1 levels were significantly decreased after treatment. No significant correlation was found between the YMRS and any of the proteins studied either before or after treatment or between IGF proteins and inflammatory markers. Discussion: To some extent, IGFBP-3 and IGFBP-5 might be further explored as potential indicators of treatment responsiveness or diagnosis biomarkers in BD.